The Assessment of Referral Practices among Basic Health Care Workers in IFO Local Government of Ogun State (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Introduction: A functional referral system is an essential component of primary healthcare delivery, ensuring continuity of care and efficient use of healthcare resources. However, in Nigeria, especially at the primary level, referral practices are often hindered by systemic, infrastructural, and human resource challenges. This study was conducted to assess the referral practices, knowledge levels, and availability of referral support tools among basic healthcare workers in Ifo Local Government Area, Ogun State, Nigeria.Objective: The main objective of the study was to assess referral practices among basic healthcare workers in Ifo Local Government. Specifically, the study aimed to examine the knowledge of referral processes, availability of referral support tools, existing referral patterns, and the challenges encountered by healthcare workers in implementing effective referral services.Method of Analysis: The study employed a descriptive cross-sectional design involving 195 healthcare workers selected through a two-stage sampling technique. A researcher-designed, structured questionnaire was used for data collection, covering knowledge, tools, practices, and challenges of referral. Data were analyzed using SPSS version 20. Descriptive statistics (frequency and percentage) were used to summarize the data, while Chi-square tests were used to assess associations between socio-demographic variables and referral knowledge, tool availability, and encountered challenges at a 0.05 significance level.Results: Findings showed that 95.4% of respondents correctly recognized referral as part of patient care, and 71.3% correctly identified referral pathways. Knowledge of referral was significantly associated with sex (p=0.018) and cadre (p=0.000). In terms of support tools, 94.9% of respondents had good availability of referral support tools, though motor vehicle availability remained low at 37.4%. Religion was the only variable significantly associated with tool availability (p=0.014). Major challenges affecting referral practice included systemic health issues (79%), facility constraints (62.6%), receiving facility readiness (76.4%), and lack of continuous quality improvement mechanisms (77.9%). However, no socio-demographic variable had a statistically significant relationship with referral challenges.Conclusion: The study concludes that although basic healthcare workers in Ifo LGA demonstrated high knowledge and reported the availability of key referral tools, systemic weaknesses continue to affect effective referral practices. Strengthening the referral system will require targeted interventions including consistent training, improved transport logistics, inter-facility communication, and supportive supervision. These improvements are vital to ensuring effective healthcare delivery and decongesting secondary and tertiary care centers in Nigeria..